Ag/AgCl@MIL-88A(Fe) heterojunction ternary composites: towards the photocatalytic degradation of organic pollutants. Issue 8 (5th February 2021) - Viswanathan, Vandana P.; Divya, K. S.; Dubal, Deepak P.; Adarsh, Nayarassery N.; Mathew, Suresh
Abstract : We have demonstrated the photocatalytic efficiency of the Ag/AgCl@MIL-88A(Fe) composite for the degradation of organic dyes and p -nitrophenol in water. Abstract : The efficient utilization of solar energy has received tremendous interest due to the increasing environmental and energy concerns. The present paper discusses the efficient integration of a plasmonic photocatalyst (Ag/AgCl) with an iron-based metal–organic framework (MIL-88A(Fe)) for boosting the visible light photoreactivity of MIL-88A(Fe). Two composites of Ag/AgCl@MIL-88A(Fe), namely MAG-1 and MAG-2 (stoichiometric ratio of Fe to Ag is 5 : 1 and 2 : 1), were successfully synthesized via facile in situ hydrothermal methods followed by UV reduction. The synthesized composite materials are characterized by FTIR, PXRD, UVDRS, PL, FESEM/EDX, TEM and BET analyses. The Ag/AgCl@MIL-88A(Fe) (MAG-2 ) hybrid system shows excellent photocatalytic activity for the degradation of p -nitrophenol (PNP), rhodamine B (RhB), and methylene blue (MB) under sunlight. We found that 91% degradation of PNP in 80 min, 99% degradation of RhB in 70 min and 94% degradation of MB in 70 min have taken place by using MAG-2 as a catalyst under sunlight. The superior activity of Ag/AgCl@MIL-88A(Fe) (MAG-2 ) is attributed to the synergistic effects from the surface plasmon resonance (SPR) of Ag NPs and the electron transfer from MIL-88A(Fe) to Ag nanoparticles for effective separation of electron–hole pairs. Furthermore, the mechanism of degradation of PNP, RhB and MB is proposed by analyzing the electron transfer pathway in Ag/AgCl@MIL-88A(Fe).